Policy assessment investment appeal of innovation projects enterprises - Andriushchenko, K.; Tepliuk, M.; Vinichenko, Igor; Nesterenko, Olena; Нестеренко, Олена Миколаївна; Нестеренко, Елена Николаевна; Yefimenko, Liudmyla; Єфіменко, Людмила Миколаївна; Ефименко, Людмила Николаевна; Budiaiev, Maksym (My University, 2019)
The aim of the article is to summarize theoretical principles and practical experience regarding the relationship between the investment attractiveness of innovative projects and economic growth. The methods of correlation and regression analysis, extrapolation and modeling are used. The subject of the study was the features and patterns of the formation, use and regulation of the policy for assessing the investment attractiveness of company’s innovative projects in modern economic conditions. In the course of the study, an algorithm was developed to assess the size and level of investment attractiveness of the algorithm is based on the allocation of components of the enterprise’s potential. It is indicated that models for evaluating efficiency and cost should take into account not only future cash flows, but also non-financial indicators. Are proposed the construction of a multivariate model based on regression analysis. The essence of this model is to combine the traditional method of correlation analysis with least squares. This approach has the main advantage - relatively high accuracy and low costs in the construction and forecasting. The proposed model of a system for ensuring the investment attractiveness of innovative projects of companies consists of two main subsystems - information-analytical and implementation-control. These blocks provide results that allow you to increase investment attractiveness, as well as timely determine the external and internal risks of the enterprise.
Keywords: investment attractiveness; innovation projects; technological advantages; the potential growth of the market; determination of risk; investment portfolio